Association of Libraries of Czech Universities - Prochásková, Iva; Landová, Hana (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
From the communist putsch in February 1948 until the end of 1989, academic libraries in the Czech Republic (formerly Czechoslovakia) were little-recognized parts of their universities. Usually situated in unsatisfactory spaces, libraries were provided with insufficient budgets and served as textbook lending offices. Access to current scientific information and knowledge was very limited - for financial and ideological reasons.